Corporate Governance and Promotion of Environmental Compliance in Uganda: A Case of National Environment Management Authority (NEMA) - Okidi, Alfred Okot (Digital Repository of Theses, 2024)
Environment degradation remains a key problem in Uganda, even after government set up the National Environment Management Authority (NEMA) in 1995 to oversee compliance to environmental guidelines and regulations by various stakeholders such as industry. The literature (including reports from NEMA) is replete with evidence of such degradation such as the destruction of swamps to make way for agriculture and industry, the destruction of natural forests by industries and communities, and poor management of industrial waste among others. To fulfill its mandate, NEMA is expected to adopt internationally recognized corporate governance principles in the conduct of its business. Further, NEMA must work closely with other arms of government to enforce compliance with environmental guidelines by various stakeholders. Based on a mixed research design, this study pursues three specific objectives. First, the study seeks to establish the extent to which the institutional context (other government agencies) curtails or enhances the operations of NEMA. Secondly, the study seeks to establish the extent to which the NEMA Board and Management have applied Corporate Governance (CG) principles. Thirdly, the study seeks to establish whether how Corporate Governance (CG) principles are applied elicits compliance in the industries. For objective one, interviews were conducted NEMA (N=10) with key informants. Qualitative data analysis using N VIVO was be conducted to see which themes emerge. For objectives two and three Structured Questionnaires were used and data was analyzed using SPSS v20.Specifically, regression analysis to establish the extent to which Corporate Governance (CG) variables influence compliance was conducted. Findings from stage one (Qualitative) revealed that institutional bottlenecks were key hindrances to environmental compliance. From Key informants, the study revealed that much as Uganda had good environmental regulations in place, the enforcement of those regulations was a challenge. Institutions were inadequately empowered and financed to enforce compliance. Furthermore, there was also a perception that the environment is a concern of NEMA rather than the host communities. The second stage of the study (Quantitative) conforms to some of the issues raised in the first stage. The study revealed that there is a positive and significant correlation between policy and training (r=0.557; r=0.553) respectively. The study further tested the effect using regression models and it revealed that training predicts compliance (Beta=0.325 p<0.000). Similarly, the policy also influences compliance (Beta=0.337; p=0.000). The study therefore highlighted that much as training and environmental policy dimensions were statistically significant, they both drive environmental compliance by 66.2%. Therefore 33.8% of environmental compliance is explained by other factors that are not covered in this study. Based on the above results, to achieve environmental compliance, there is a need for policymakers to enhance the capacity of environmental enforcement agencies. Secondly, much as some industries indicated having environmental compliance policies in place, there is a need to formulate an economic benefit for compliance to enhance self-compliance among various firms.